PERANCANGAN SISTEM E-COMMERCE PADA TOKO MADU AL-FURQON JAMBI - Riswan, Riswan; Nilawati, Nilawati (JURNAL AKADEMIKA, 2024)
Implementation of E-Commerce As Online Sales Media. The purpose of this research is to implement e-commerce website that serves as a media promotion and electronic sales. And know the obstacles faced in implementing e-commerce website. The type of research conducted is qualitative. This study took a case study at the shop Madu Al-Furqon Jambi. Techniques Data collection conducted by researchers using observation, interviews and documentation. The results of the research using e-commerce implementation by using online sales at Madu Al-Furqon Jambi store will be able to help reduce the cost incurred and can convey information in detail and quickly about the product to the customer, Based on the results of this study is expected to help shop Madu Al-Furqon Jambi to get maximum results and can compete with similar stores.